The Presence of Fucogalactoxyloglucan and Its Synthesis in Rice Indicates Conserved Functional Importance in Plants. Issue 2 (13th April 2015) - Liu, Lifeng; Paulitz, Jonathan; Pauly, Markus
Abstract : A tissue-specific cell wall fucogalactoxyloglucan is present in rice. Abstract: The predominant structure of the hemicellulose xyloglucan (XyG ) found in the cell walls of dicots is a fucogalactoXyG with an XXXG core motif, whereas in the Poaceae (grasses and cereals), the structure of XyG is less xylosylated (XXGGn core motif) and lacks fucosyl residues. However, specialized tissues of rice ( Oryza sativa ) also contain fucogalactoXyG . Orthologous genes of the fucogalactoXyG biosynthetic machinery of Arabidopsis ( Arabidopsis thaliana ) are present in the rice genome. Expression of these rice genes, including fucosyl-, galactosyl-, and acetyltransferases, in the corresponding Arabidopsis mutants confirmed their activity and substrate specificity, indicating that plants in the Poaceae family have the ability to synthesize fucogalactoXyG in vivo. The data presented here provide support for a functional conservation of XyG structure in higher plants.